تمويل الجمعيات الرياضية ودوره في دعم الأندية الرياضية لدى الفرق الشابة - ديمح الطاهر; سليمان قاضي مؤمن (My University, 2025)
هدفت هذه الدراسة إلى الكشف عن دور تمويل الجمعيات الرياضية في دعم الأندية الرياضية لدى الفرق الشابة من خلال دراسة ميدانية لعينة من المدربين ومسؤولي الفرق الرياضية التابعة لمديرية الشباب والرياضة بولاية الأغواط في ضوء المعطيات النظرية والتحليلية التي تم التوصل إليها من خلال هذه الدراسة يتضح أن مسألة تمويل الجمعيات الرياضية تمثل إحدى الركائز الأساسية في دعم الأندية الرياضية لا سيما تلك الموجهة للفئات الشابة، لقد أظهرت نتائج الدراسة التي استندت إلى آراء المدربين والمسؤولين التابعين لمديرية الشباب والرياضة بالأغواط أن هناك علاقة طردية قوية بين حجم ونوعية التمويل الموجه للجمعيات الرياضية وبين قدرة هذه الجمعيات على تحقيق أهدافها التكوينية والرياضية خاصة فيما يتعلق بتوفير التجهيزات واستقرار الطاقم الفني وضمان استمرارية البرامج التدريبية. وقد تبين من خلال تحليل البيانات الإحصائية باستخدام معامل بيرسون أن التمويل لا ينعكس فقط على الجوانب المادية، بل يتعدى ذلك ليؤثر بشكل مباشر على البيئة التدريبية العامة وعلى مدى تحفيز الفرق الشابة للانخراط الجاد في الممارسة الرياضية، كما أشارت نتائج الفرضيات الجزئية إلى محدودية التمويل العمومي وعدم كفايته لتغطية المتطلبات الأساسية الأمر الذي يستدعي البحث عن بدائل تمويلية مستدامة إلى جانب تحسين آليات التسيير المالي والشفافية في التوزيع. إن تحقيق فعالية الجمعيات الرياضية لا يمكن فصله عن مدى جاهزية منظومتها التكوينية والتنظيمية والتي تتطلب بدورها تمويلًا مستقرًا وعقلانيًا يستجيب لحاجات الميدان، كما أن إشراك الإطارات الرياضية في وضع الأولويات وضمان رقابة مالية فعّالة عوامل أساسية لتعزيز فعالية الدعم المالي وتحقيق الأهداف الاستراتيجية في تكوين الفرق الشبانية وتطويرها.
دراسة ميدنية على عينة من مسؤولي الفرق التابعة لمديرية الشباب والرياضة لولاية الأغواط
This study aimed to reveal the role of funding sports associations in supporting sports clubs for youth teams through a field study of a sample of trainers and officials of sports teams affiliated with the Directorate of Youth and Sports in the Governorate of Laghouat. In light of the theoretical and analytical data obtained from this study, it is clear that the issue of funding sports associations represents one of the fundamental pillars in supporting sports clubs, especially those directed towards youth groups. The results of the study, which were based on the opinions of trainers and officials from the Directorate of Youth and Sports in Laghouat, showed that there is a strong direct relationship between the volume and quality of funding directed to sports associations and the ability of these associations to achieve their training and sports goals, particularly concerning the provision of equipment, stability of the coaching staff, and ensuring the continuity of training programs.It was found through the analysis of statistical data using the Pearson correlation coefficient that funding does not only reflect on the material aspects, but rather transcends to directly affect the overall training environment and the extent to which youth teams are encouraged to engage seriously in sports practice, as indicated by the results. ... The effectiveness of sports associations cannot be separated from the readiness of their training and organizational systems, which in turn require stable and rational funding that meets field needs. Additionally, involving sports officials in setting priorities and ensuring effective financial oversight are essential factors to enhance the effectiveness of financial support and achieve strategic goals in the formation and development of youth teams.